BYOND BSI Mobile Banking Usability Marginal Category with SUS 63.42: Usabilitas Mobile Banking BYOND BSI Kategori Marginal dengan SUS 63,42 - Herawati, Nadia; Septiadi, Jaka (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Digital transformation in Islamic banking requires mobile banking applications with high usability to ensure customer satisfaction. Specific Background: BYOND by BSI represents a flagship mobile banking platform whose usability determines user acceptance and service quality. Knowledge Gap: Previous studies mainly evaluated older versions or competitor applications, leaving a lack of comprehensive and recent usability assessment of the re-branded BYOND by BSI. Aims: This study aims to measure the usability level of BYOND by BSI and identify interface interaction barriers using System Usability Scale (SUS) and Heuristic Evaluation (HE). Results: Findings show a SUS score of 63.42, placing the application in the “Marginal” acceptability category with “OK” rating (Grade C-), supported by heuristic issues such as linear navigation, inconsistent visual feedback, limited user control, absence of shortcut features, and inadequate help access. Novelty: The study integrates user-based SUS measurement with expert-based heuristic evaluation to provide a comprehensive usability analysis of a re-branded Islamic mobile banking application. Implications: The results provide a structured roadmap for interface redesign, focusing on navigation improvement, visual consistency, and feature optimization to achieve the acceptable usability threshold (72.6) and improve user experience quality. Highlights SUS score indicates usability positioned below acceptable threshold Interface issues identified in navigation structure and visual feedback consistency Integrated evaluation reveals detailed technical barriers from user and expert perspectives KeywordsSystem Usability Scale; Heuristic Evaluation; Usability; BYOND BSI; Islamic Mobile Banking